Μετατροπή διοξειδίου του άνθρακα σε μεθάνιο με χρήση αναερόβιας βιομάζας και μηδενικού σιδήρου ή μαγνησίου - Φιλιππέτη, Άντρια (Τμήμα Επιστήμης και Τεχνολογίας Περιβάλλοντος, Σχολή Γεωτεχνικών Επιστημών και Διαχείρισης Περιβάλλοντος, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2018)
Research to detect different renewable sources of energy is necessary to replace the already harmful sources of the environment. This makes it necessary for scientists to be committed to creating new guidelines for study to solve ecological problems. In the present study, emphasis is placed on the Anaerobic digestion process through conductive materials such as ferrous iron (Fe0) and magnesium (Mg0) for electron transfer and mixed culture from anaerobic biomass to convert carbon dioxide and hydrogen to methane. The first experimental test focuses on finding the appropriate concentration of anaerobic mixed culture biomass under specific conditions. It consists of two more iterations by keeping the conditions in the sampling room to stay the same and to re-add carbon dioxide as an organic source for the feeding of anaerobic biomass. The purpose of the first experiment is to find the best conditions that can be used for optimum methane production, namely the optimal amount of granular sludge. The purpose of repeating the experiment by feeding the samples with carbon dioxide is to check if the methane values can reach the same concentrations as the original and if so, how long that can be done as the remaining variables in sample space remain the same. Finally, it is important to note that all three trials have been studied at the same time. The 2nd experimental test is Magnesium (Mg0) that is conductive and optimizes and accelerates the generation of hydrogen in the sample space for the ultimate conversion to methane via anaerobic digestion.
Keywords: Anaerobic digestion; Anaerobic biomass; Methane; Magnesium; Hydrogenotrophic methanogens; Granular sludge; Conversion; Αναερόβια χώνευση; Αναερόβια βιομάζα; Μεθάνιο; Μαγνήσιο; Υδρογονοτρόφοι μεθανογόνοι; Κοκκώδης λάσπη; Μετατροπή